دور القاضي في تسوية المنازعة البيئية وفقاً لمتشريع الج ا زئري - عازب عثمان, انتصار; بن عمر, سمر; رزاق لبزة, منال (University of Eloued جامعة الوادي, 2023)
إن الحفاظ عمى بيئة إنسانية نظيفة وخالية من المموثات ىو أحد ميام ومسؤوليات الدولة الحديثة، غير أن الحل الأمثل يكون بالوقاية من الاض ا رر البيئية والحفاظ عمييا، في ىذا السياق يأتي موضوع بحثنا الموسوم ب: دور القاضي في تسوية المنازعة البيئية وفقا لمتشريع الج ا زئري. ورغم الطابع الاجتيادي لمقضاء الإداري، فقد سجمنا التكيف المحدود لقواعد المسؤولية الإدارية مع مجال حماية البيئة، سواء من حيث الأساس الذي تقوم عميو ىذه المسؤولية، أو من حيث نظام التعويض عن الاض ا رر البيئية، لما تتميز بو ىذه الأخيرة من خصائص تختمف عن خصائص الضرر المتعارف عميو، وىو ما يدفع إلى ضرورة تفعيل مبادئ القانون البيئي، لتطوير قواعد المسؤولية الإدارية في ىذا المجال.Preserving a clean human environment free of pollutants is one of the tasks and responsibilities of the modern state, but the best solution is to prevent and preserve environmental damage. Despite the jurisprudential nature of the administrative judiciary, we have recorded the limited adaptation of the rules of administrative responsibility to the field of environmental protection, both in terms of the basis on which this responsibility is based, or in terms of the system of compensation for environmental damage, because of the characteristics of the latter that differ from the characteristics of the damage known to us. , which prompts the need to activate the principles of environmental law, to develop the rules of administrative responsibility in this field.
مذكرة ماستر
Keywords: البيئة، الن ا زع البيئي، التعويض النقدية; environment, environmental conflict, cash compensation